Predictors of respiratory cancer-related mortality for Jews and Arabs in Israel - Ronit Pinchas-Mizrachi; Ephraim Shapiro; Ayal Romem; Beth G. Zalcman (Elsevier, 2021)
Background: Respiratory cancers, including lung, tracheal and bronchus cancers, are a leading cause of cancer-related mortality in Israel; however, incidence can differ among demographic groups. Despite the importance of sociodemographic characteristics and the interactions between them to incidence and mortality, this topic is understudied. This study analyzes sociodemographic disparities by sex and ethnicity among Jews and Arabs to understand cancer outcome differences stratified by SES, marital status, and number of children as potential contextual factors. Methods: This retrospective cohort study analyzed respiratory cancer-related mortality rates among Israelis born between 1940 and 1960 over 21-years. The follow up period was between January 1, 1996 and 12.31.2016. Mortality rates for Jews and Arabs were calculated. Using a Cox Regression, a multivariate model was constructed to determine the association between ethnicity and respiratory cancer mortality. The study population was then divided into four groups, by sex and ethnicity, to determine the association between marital status, number of children, and SES with respiratory cancer mortality for each subgroup. Results: The overall mortality rate was 0.6%. Arabs had higher mortality rates compared to Jews, even after adjusting for demographic factors including age, sex and SES (Adjusted Hazard Ratio (AHR) = 1.442, 99% confidence intervals (CI) = 1.354,1.546). Among men, a higher mortality rate was found among Arabs (AHR = 1.383, 99%CI = 1.295,1.477), while among women, Arabs had lower mortality rates (AHR = 0.469, 99%CI = 0.398,0.552). Significant mortality rate differences were observed by ethnicity and sex for each sociodemographic variable. Conclusions: This study highlights the importance and implications of understanding differences in respiratory cancer mortality between Jews and Arabs, a minority group in Israel, and is relevant for minority groups in general. There is a need to tailor interventions for these groups, based on differing underlying causes and contextual factors for these cancers. Cancer outcomes among these groups should also be studied separately, by sex, to better understand them.